Malaysian consumers’ willingness-to-pay for functional food. - Phuah, Kit Teng; Rezai, Golnaz; Mohamed, Zainalabidin; Shamsudin, Mad Nasir (2012)

(untitled)
Consumers are changing their eating habits and paying more attention to food quality or food safety and are looking beyond the basic nutritional benefits as a way to improve their quality of life and for extending their life expectancy. These phenomena provide a great market opportunity for developing the functional food industry in Malaysia. The objective of this study is to determine the WTP of consumers towards functional food given the benefits of such types of food to their health and well being. A survey was conducted in the Klang Valley, Malaysia and contingent valuation method (CVM) was used to determine the consumers’ WTP for functional food. Descriptive analysis, factor analysis and binary logistic model was used in this study. The results indicated that the majority of the respondents had a high level of willingness to pay for functional food. Six latent factors which influence the consumers’ WTP for functional food were identified by using factor analysis were identified. These were; food safety, consumers’ preferences, health consciousness, knowledge towards functional food, product price and functional food attributes. Concerning the binary logistic model, the result showed that gender, income, age, food safety, consumers’ preferences, health consciousness, product price and functional food attributes significantly influenced the consumers’ WTP for functional food.